Blockade of the AMPA receptor prevents CA1 hippocampal injury following severe but transient forebrain ischemia in adult rats. - Buchan, A; Li, H; Cho, S; Pulsinelli, W (1991)
The cytoprotective effect of NBQX, a selective AMPA receptor antagonist, was tested following 10 min of severe forebrain ischemia using the 4-vessel occlusion model. Immediately, and at 15 and 30 min following reperfusion, adult Wistar rats received intraperitoneal injections of either saline (n = 5), 1 mg lithium chloride (n = 17) or 30 mg/kg of the lithium salt of NBQX (n = 18). In saline-treated animals 82 +/- 12% of CA1 hippocampal neurons were lost. Of those treated with lithium 70 +/- 23% were injured, while those given NBQX sustained only 40 +/- 34% CA1 necrosis (P less than 0.01). Twelve of 18 NBQX-treated animals had less than 30% CA1 injury as compared with 1 of 17 lithium-treated animals. The AMPA receptor may play a more important role than the NMDA receptor in selective ischemic necrosis of hippocampal neurons.